2023
DOI: 10.1111/aji.13670
|View full text |Cite
|
Sign up to set email alerts
|

New immune horizons in therapeutics and diagnostic approaches to Preeclampsia

Abstract: Hypertensive disorders of pregnancy (HDP) are one of the commonest maladies, affecting 5%–10% of pregnancies worldwide. The American College of Obstetricians and Gynecologists (ACOG) identifies four categories of HDP, namely gestational hypertension (GH), Preeclampsia (PE), chronic hypertension (CH), and CH with superimposed PE. PE is a multisystem, heterogeneous disorder that encompasses 2%–8% of all pregnancy‐related complications, contributing to about 9% to 26% of maternal deaths in low‐income countries an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 253 publications
(430 reference statements)
0
5
0
Order By: Relevance
“…Growing evidence suggests that trophoblast necrotizing apoptosis plays a complex role in preeclampsia, involving superficial trophoblast infiltration and inadequate uterine artery remodeling ( 18 ). This may be closely related to disorders outside the immune system, caused by abnormal immune system activation and unbalanced differentiation of T cells ( 19 , 20 ). The GO analysis revealed the enrichment of biological functions related to cytolysis, inflammatory cell differentiation, regulation of adaptive immune response, and cell-matrix adhesion, thereby emphasizing the pivotal role of immune-related processes in placental pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that trophoblast necrotizing apoptosis plays a complex role in preeclampsia, involving superficial trophoblast infiltration and inadequate uterine artery remodeling ( 18 ). This may be closely related to disorders outside the immune system, caused by abnormal immune system activation and unbalanced differentiation of T cells ( 19 , 20 ). The GO analysis revealed the enrichment of biological functions related to cytolysis, inflammatory cell differentiation, regulation of adaptive immune response, and cell-matrix adhesion, thereby emphasizing the pivotal role of immune-related processes in placental pathology.…”
Section: Discussionmentioning
confidence: 99%
“…58 MHC class I plays an essential role in maternal-fetal immune balance. 10,62 Additionally, T cells are crucial adaptive immune cells during pregnancy, and their abnormal activation is closely related to preeclampsia onset. 10,28 Here, we also indicated that CCR, para-inflammation, MHC class I and T cell costimulation probably are the main immune pathways that contribute to pathological process of EOPE.…”
Section: F I G U R E 5 Legend On Next Pagementioning
confidence: 99%
“…Different fetal growth parameters showed association with gestational age specific combination of cytokines. Karmakar et al., have informed several aberrations of the immune system including increased intracellular production of complement protein C5a, imbalanced differentiation of T cells, altered distribution of Tregs and suboptimal production of immunosuppressive cytokines like IL‐10, IL‐4 and IL‐13 in women suffering from gestational hypertensive disorder, Preeclampsia (PE) 22 . This deeper insight into immune anomalies in PE has led to evaluation of novel therapeutic candidates for PE management.…”
Section: Immune Dysregulation During Pregnancy: Recurrent Pregnancy L...mentioning
confidence: 99%